2001
DOI: 10.2214/ajr.176.5.1761313
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy for Detection of Simulated Lesions

Abstract: We developed software with which we can generate brain images of a wide range of pulse sequences and that allows us to specify the location, size, shape, and intrinsic characteristics of simulated lesions. We found that the use of FLAIR sequences increases detection accuracy for cortical-subcortical and periventricular lesions over that associated with proton density- and T2-weighted sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Further studies should be designed to show if this protocol could be further streamlined. For brain assessment, we found that, in accordance with the findings of other investigators, T1-weighted inversion-recovery prepared spoiled gradient-echo and T2-weighted FLAIR sequences are important in the detection of white matter lesions (24) and that three-dimensional arterial spin labeling sequences are important in identification of cerebral blood flow abnormalities (25). Our quantitative susceptibility map sequence did not show any hemorrhage in the brain, and diffusion-tensor and resting-state functional MR imaging sequences have not, to our knowledge, been studied extensively in pediatric cancer survivors, although some investigators suggest that they are potentially useful (26,27).…”
Section: Discussionsupporting
confidence: 85%
“…Further studies should be designed to show if this protocol could be further streamlined. For brain assessment, we found that, in accordance with the findings of other investigators, T1-weighted inversion-recovery prepared spoiled gradient-echo and T2-weighted FLAIR sequences are important in the detection of white matter lesions (24) and that three-dimensional arterial spin labeling sequences are important in identification of cerebral blood flow abnormalities (25). Our quantitative susceptibility map sequence did not show any hemorrhage in the brain, and diffusion-tensor and resting-state functional MR imaging sequences have not, to our knowledge, been studied extensively in pediatric cancer survivors, although some investigators suggest that they are potentially useful (26,27).…”
Section: Discussionsupporting
confidence: 85%
“…However, the specificity of PVL for MS among patients with neurological diseases has not been systematically addressed [3]. FLAIR provides increased sensitivity of demyelinating lesion detection especially in the periventricular location as it can differentiate the signal from the CSF, in the lateral ventricles, from the lesion itself [16-18]. Another important issue is the presence of nonspecific T2 hyperintensities adjacent to the frontal horns of the lateral ventricles in healthy subjects, so-called frontal capping, which can be mistakenly counted as PVL [12].…”
Section: Discussionmentioning
confidence: 99%
“…Note that because the segmentation operates strictly on the vector of FLAIR intensity values, it was not necessary to mimic the size or shape characteristics of typical WMH (eg, Ref. 21). …”
Section: Methodsmentioning
confidence: 99%